Implementasi IoT Pada Sistem Palang Pintu RFID Otomatis Berbasis ESP32 Dengan Integrasi Database Cloud Google Sheets - Desmi Maharani; Muhammad Iqrom Januardandi Dharmawan; Taufik Arrahman; Agus Priyansah; Febbio Titian Wijaya; Hibramsyah -; Azwa Sasta Amelia; Abdul Rahman (MDP Student Conference, 2026)
This study aims to design and implement an automatic parking gate system based on the Internet of Things (IoT), which enables real-time access control and data logging. The proposed system integrates Radio Frequency Identification (RFID) for vehicle authentication, an ESP32 microcontroller as the main controller, and a cloud-based spreadsheet database for data storage. The research method uses a quantitative experimental approach through hardware and software implementation followed by functional testing. The system was evaluated by testing registered and unregistered RFID cards, gate opening and closing duration, vehicle detection, and real time data recording. Experimental results show that the system achieves 100% accuracy in access validation, where registered cards successfully open the gate, while unregistered cards are rejected and indicated by an audible alert. All access data are recorded reliably in real time. The results indicate that the proposed system is responsive, secure, and suitable for small- to medium-scale parking access management.